2013
DOI: 10.1002/cmdc.201300217
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of NVP‐LEQ506, a Second‐Generation Inhibitor of Smoothened

Abstract: First disclosure: Continued optimization provided a novel type of Smoothened (Smo) antagonist based on a pyridazine core. The compound, NVP‐LEQ506, currently in phase I clinical trials, combines high intrinsic potency and good pharmacokinetic properties resulting in excellent efficacy in rodent tumor models of medulloblastoma. Activity against a Smo mutant conferring resistance observed in a previous clinical trial with a competitor compound suggests additional therapeutic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…We hypothesize that this interaction restrains the orientation of LY2940680, which leads to a shift of the phthalazine core of LY2940680 away from D473 6.55 compared to Anta XV, weakening the role of D473 6.55 in ligand binding. This reduced involvement of D473 6.55 in binding might also underlie the effect of chemical modifications on existing compounds which could overcome the drug resistant mutation D473 6.55 H as shown in studies with derivatives of GDC-0449 12 and Anta XV 14 . The long and continuous cavity straddling the ECL region and 7TM domain of SMO provides a variety of binding sub-sites suitable for ligand interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that this interaction restrains the orientation of LY2940680, which leads to a shift of the phthalazine core of LY2940680 away from D473 6.55 compared to Anta XV, weakening the role of D473 6.55 in ligand binding. This reduced involvement of D473 6.55 in binding might also underlie the effect of chemical modifications on existing compounds which could overcome the drug resistant mutation D473 6.55 H as shown in studies with derivatives of GDC-0449 12 and Anta XV 14 . The long and continuous cavity straddling the ECL region and 7TM domain of SMO provides a variety of binding sub-sites suitable for ligand interaction.…”
Section: Discussionmentioning
confidence: 99%
“…This is not only important for understanding the structure-activity relationships (SAR) of chemically distinct SMO ligands, but also for providing a mechanistic understanding of chemoresistant mutations. For example, the D473 6.55 H (superscripts indicate residue numbering using the Ballesteros-Weinstein nomenclature for class F receptors 9,10 ) mutation in human SMO makes antagonists such as GDC-0449 unable to inhibit the receptor 11 ; while several other compounds are insensitive to this drug resistance mutation 1214 . Delineating the structural basis for the differential effects of mutations on diverse ligands would provide a rational platform for the development of drugs to counteract emerging drug resistance effects.…”
Section: Introductionmentioning
confidence: 99%
“…It was subsequently shown that MK-4101 inhibited Hh signaling both in a reporter gene assay in an engineered mouse cell line (Gli_Luc) with IC 50 ¼ 1.5 mmol/L ( (27). While vismodegib showed a 100-fold loss of affinity for the resistant D477G mutant in binding assays, MK-4101 only showed a 15-fold decrease in affinity (Table 3), suggesting MK-4101 as a potential therapeutic agent for vismodegib or sonidegib resistant tumors (28).…”
Section: Identification Of Mk-4101 As a Smo-binding Inhibitormentioning
confidence: 99%
“…LEQ506 (3a), a second-generation Hh inhibitor, is currently being investigated in a Phase I clinical trial for patients with solid tumors. SAR studies had demonstrated the replacement of the benzylic methylene linker with an oxygen atom (3b) was well tolerated, whereas replacement with an NH group (3c) resulted in a 10-fold decrease in inhibition of the Hh pathway [15].…”
Section: Introductionmentioning
confidence: 99%